Inserción de los profesionales sanmarquinos en el mercado laboral global, 2010-2015. Un estudio de casos hacia una visión sociohistórica prospectiva - Ríos Burga, Jaime (2017)
The labor market today in the global labor market professionals San Marcos professionals show a still predominantly male but the trend structuring in the growing female incorporation into a structural situation of reduced obtaining degrees and diplomas of graduates, and doctoral students, mastership. As the importance for job access and training experience applied in professional careers. For which graduates in the absence of an institutional and policy labor incorporation create their own strategies in line with the skills and technical capabilities, in addition to the professional title obtained and the accumulated work experience. Situation that determines your level of income and professional expectations, increasing flexibility and privatization in the global labor market.